MULTICULTURALISM IN GLOBALIZATION ERA: HISTORY AND CHALLENGE FOR INDONESIA - Habib Zarbaliyev (Journal of Social Studies (JSS), 2017)
Indonesia is multicultural country in which the conflicts between etchnics may occur. With regard to this, Indonesia must implement a multicultural education which focuses on (1) regions, ethnics and traditions; (2) faith; and (3) tolerance. In addition, Indonesia must assure multicultural security for its citizens, such as, keeping energy security, economic security and cultural security. This will provide a solution to the conflicts, or significantly minimize possibility of conflicts to occur.  The current globalization process does not repel isolative condition, nor enable cultural development strangely. In this condition, the strategy to prevent cultural conflicts is to perform a dialogue between cultures.